Analysis of the Application of Management Accounting on Production Cost Efficiency at PT Indofood Sukses Makmur Tb - Aliffia Rosada Nibros; Afifah Puti Salamah; Dina Era Ermawati; Muhammad Rahman; Sukamah S; Sri Utami; Hendra Lesmana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the application of management accounting practices in improving production cost efficiency at PT Indofood Sukses Makmur Tbk, one of Indonesia’s largest consumer goods manufacturers. Using a qualitative descriptive approach, the research analyzes secondary data derived from annual and financial reports from 2022–2025. The study explores the implementation of budgeting, variance analysis, flexible budgeting, responsibility accounting, and Activity-Based Costing (ABC) as key instruments for cost control. Findings show that Indofood has adopted management accounting techniques comprehensively to monitor production activities, allocate resources efficiently, and identify cost deviations. Although total production costs increased annually, the rate of increase declined, indicating improved cost efficiency supported by more accurate cost measurement and strengthened cost-control mechanisms. The company’s ability to align actual costs below budgeted amounts further reflects effective managerial oversight. Overall, the application of management accounting significantly contributes to optimizing material usage, labor, and overhead expenses, while enhancing operational decision-making. The study recommends continuous evaluation of cost variance and encourages future research using primary data to provide deeper insights into the strategic role of management accounting in production efficiency.